Kebab Bistro / Tengku Nur Akasyah Tuan Soh … [et al.] - Tuan Soh, Tengku Nur Akasyah; Norzelan, Nurdina Husna; Salim, Intan Zulaikha; Razak, Nurul Huda; Anuar, Muhammad Izzudin (2022)
The Kebab Bistro Restaurant is a new business that will be operated in Seri Iskandar Perak, Malaysia. This is a partnership business where our specialization is in the Food and Beverage (FNB) industry. Kebab Bistro Restaurant is also a franchise business. The name of our company come up from the idea of our group member during the brainstorming session. To illustrate, each of us has a responsibility to grow this business and together in facing any problems. We decided to name it as Kebab Bistro because it is unique and attractive word which the word ‘Bistro’ means a small and inexpensive restaurant in which we provide an affordable price for the customer to purchase. Besides, it is an easy phase to be remember among the customers. As for business, we will be providing a kebab with various taste of flavor. The reasons we start up this kebab business idea is because after we did some research survey among the societies in Malaysia which shows that they love to eat kebab either during breakfast, lunch, dinner, or over late night-time in a like manner this illustrate a higher demand. Hence, we take this opportunity to create a food that people can enjoy eating it at any time. Additionally, the market size of the business is suitable for all level of ages. Not to mention the products of our business will be using a high-quality ingredient.